2015
DOI: 10.1371/journal.pone.0136419
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Next-Generation Sequencing Assay for BRCA1 and BRCA2 Variants for the Clinical Laboratory

Abstract: The objective of this study was to design and validate a next-generation sequencing assay (NGS) to detect BRCA1 and BRCA2 mutations. We developed an assay using random shearing of genomic DNA followed by RNA bait tile hybridization and NGS sequencing on both the Illumina MiSeq and Ion Personal Gene Machine (PGM). We determined that the MiSeq Reporter software supplied with the instrument could not detect deletions greater than 9 base pairs. Therefore, we developed an alternative alignment and variant calling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
10
35
0
5
Order By: Relevance
“…Our method reliably estimates gene copy number changes from amplicon-based targeted NGS with the acquired results being comparable with widely used assays, including exome sequencing, aCGH, digital droplet PCR, and FISH (17). Critically, the data processing time for this panel-based CNA estimation is substantially shorter of that for exome sequencing and can be easily completed even with a personal computer.…”
Section: Discussionmentioning
confidence: 69%
“…Our method reliably estimates gene copy number changes from amplicon-based targeted NGS with the acquired results being comparable with widely used assays, including exome sequencing, aCGH, digital droplet PCR, and FISH (17). Critically, the data processing time for this panel-based CNA estimation is substantially shorter of that for exome sequencing and can be easily completed even with a personal computer.…”
Section: Discussionmentioning
confidence: 69%
“…Several next‐generation sequencing (NGS) approaches to determine the mutation status of BRCA1 and BRCA2 have been developed, but most approaches were validated using high‐quality DNA (i.e., blood‐derived DNA) [Feliubadalo et al., 2013; Hirotsu et al., 2015; Strom et al., 2015]. Therefore, these approaches can successfully be implemented in a diagnostic setting to screen for germline defects in BRCA1 and BRCA2 using blood‐derived DNA [D'Argenio et al., 2015; Trujillano et al., 2015], but cannot be used to sequence low quality and highly fragmented DNA derived from FFPE tumor blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several findings on HBC with NGS, a recent study demonstrated that with regard to the two most common platforms, neither the Illumina MiSeq sequencer with the supplied MiSeq Reporter software nor the Life Technologies Ion Torrent Personal Genome Machine (Ion PGM) with the supplied Torrent Suite software were completely suitable for clinical laboratory sequencing of BRCA1 or BRCA2 10. The inability of the MiSeq system is that it fails to detect insertions and deletions larger than nine base pairs.…”
Section: Ngs Analysis For Solid Cancer Diagnosismentioning
confidence: 99%